Mechanism of Valence Change in Mandailing Language: Linguistics Typology - Ernita Daulay; Mulyadi Mulyadi (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2021)
This paper described the mechanism of valence change in Mandailing language. The concept of valence refers to the number of arguments a verb that serves as a predicate in a clause can present. Changing the valence of verbs in Mandailing through a causative process causes the verbs to experience an increase in valence. This study was included a qualitative descriptive study, in which the method is a study of language typology and the data analyzed based on the problems discussed using the method Agih. The results of the data analysis of this study are presented using an informal method in the form of explanation or exposure using ordinary words or verbal language. The determinants used by this method are the language elements in the Mandailing language. The purpose of this study was to find what types of verbs in the Mandailing language can experience changes in valence, symptoms, and their process of change, and the semantic role of these verbs. The data analysis from this study was obtained through the observation method and the proficient method with informants; based on the results of the analysis, it can be concluded that changes in the valence of the Mandailing language occur mainly in intransitive, transitive, transitive verbs, which are grouped into symptoms that cause valence reduction and valence expansion. This study is also expected to inspire some researchers interested in the mechanism of valence change in Mandailing language, either micro or macro.